2017
DOI: 10.1111/conl.12426
|View full text |Cite
|
Sign up to set email alerts
|

Mobilizing volunteers to sustain local suppression of a global marine invasion

Abstract: Species invasions often occur at geographic scales that preclude complete eradication, setting up long-term battles for population control. To understand the extent to which exotic species removal by volunteers can contribute to local invasion suppression and alleviate invasion effects, we studied the activities of volunteers culling invasive lionfish during annual "derby" events in the Atlantic. From 2012 to 2014, single-day derbies reduced lionfish densities by 52% over 192 km 2 on average each year. Differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 44 publications
1
38
0
1
Order By: Relevance
“…Por el contrario, Capurganá e isla Fuerte son lugares remotos que carecen de figuras de protección y donde la presencia de buzos es escasa; por lo tanto, las acciones de control de las poblaciones del invasor han sido prácticamente inexistentes. Diferentes estudios en el AO destacan la necesidad de controlar el número de peces león mediante la cacería constante y los torneos de pesca, que son quizás las únicas acciones disponibles hasta la fecha para enfrentar la invasión biológica por P. volitans (Barbour et al, 2011;Frazer et al, 2012;De León et al, 2103;Green et al, 2017). all this variability in lionfish abundance estimates, even in one location, can be a reflection of highly dynamic populations due to variations in reproductive effort and recruitment success versus natural mortality, plus fishing mortality caused by differential control efforts in each locality.…”
Section: Localidad/localityunclassified
See 1 more Smart Citation
“…Por el contrario, Capurganá e isla Fuerte son lugares remotos que carecen de figuras de protección y donde la presencia de buzos es escasa; por lo tanto, las acciones de control de las poblaciones del invasor han sido prácticamente inexistentes. Diferentes estudios en el AO destacan la necesidad de controlar el número de peces león mediante la cacería constante y los torneos de pesca, que son quizás las únicas acciones disponibles hasta la fecha para enfrentar la invasión biológica por P. volitans (Barbour et al, 2011;Frazer et al, 2012;De León et al, 2103;Green et al, 2017). all this variability in lionfish abundance estimates, even in one location, can be a reflection of highly dynamic populations due to variations in reproductive effort and recruitment success versus natural mortality, plus fishing mortality caused by differential control efforts in each locality.…”
Section: Localidad/localityunclassified
“…On the contrary, Capurganá and Fuerte island are remote places without protection status and where the presence of divers is scarce; therefore, control actions of the invader populations have been practically nonexistent. Different studies in the WA stand out the need of controlling lionfish numbers through constant culling and derbies, which are maybe the only actions available until date to face the biological invasion by P. volitans (Barbour et al, 2011;Frazer et al, 2012;De León et al, 2103;Green et al, 2017).…”
Section: Localidad/localitymentioning
confidence: 99%
“…Perhaps the most widely bruited proposal for physical control of a marine invader is the contention that the western Atlantic invasion by lionfishes, Pterois volitans (Linnaeus, 1758) and P. miles (Bennett, 1828), can be controlled through spearing and/or netting by trained divers or volunteers, or by lionfish “derbies.” Both enthusiasts and skeptics agree that wide-scale control throughout their entire invasive range is unattainable by this means, but Green et al ( 2014 ) and Côté et al ( 2014 ) suggest that this method can maintain lionfish populations on local reefs at relatively innocuous densities. They tested the approach in a controlled experiment conducted by NGO and university scientists with monthly culling by trained divers for 1.5 years on a series of Bahamian reefs (Green et al, 2014 ), rejected the contention that culling-induced lionfish behavioral shifts defeat the method (Côté et al, 2014 ), and found evidence from six single-day derbies that such events can often suppress densities below levels detrimental to native fish populations (Green et al, 2017 ). However, these are all so far short-term efforts, and Barbour et al ( 2011 ) argue that sustained intense pressure would be needed to effect long-term control.…”
Section: Maintenance Managementmentioning
confidence: 99%
“…As a single example, from 2009 to 2012, volunteer divers with the Reef Environmental Education Foundation surveyed for and removed 960 lionfish from 20 sites along BBR, with annual removal increasing from zero lionfish in 2009 (when none were sighted) to 63 lionfish in 2010, peaking at 505 in 2011, and dropping to 392 lionfish in 2012. A recent evaluation of culling efficacy from Florida and the Bahamas has demonstrated that even a single-day culling event can reduce lionfish densities below the threshold at which they are predicted to overconsume native prey (Green, Underwood & Akins, 2017). Rather than challenge existing evidence of lionfish effects, the results of Hackerott et al (2017) may therefore highlight a case of successful regional management of lionfish along the BBR.…”
Section: Evaluating Lionfish Predatory Effectsmentioning
confidence: 99%